The Legal Certainty on Freedom of Foreign Football Player Transfer in Indonesia: Learning of Bosman Ruling - Rizki Habibulah; Ming-Hsi Sung (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
The Bosman ruling means that players could move or transfer to a new club at the end of their contract without paying their former clubs any fee. A player can now agree with a pre-contract with another club for a free transfer if the players' contract with their existing club has six months or less remaining. This means that the Bosman Rulingis a pioneer in the freedom of contract aspect in sports law. According to Law Number 3 of 2005 on National Sports System in Indonesia, the problem in Indonesia is that there is no regulation regarding the freedom of contract for the sporting member in Indonesia. Some cases violate the Bosman Ruling against foreign football players Damian Linzio. Damian Linzio cannot solve his problems because there is no regulation related to Bosman Ruling issues in Indonesia. This Research aims to adapted Bosman Ruling into Indonesian Sports Law based on Law Number 3 of 2005 concerning the National Sports System. Bosman Ruling is very important in sports law because it regulates the freedom of contract. The type of this research is normative legal research. Normative legal research is a process to find the rule of law, principles of law, and the legal doctrines to address the legal issues faced equal treatment of foreign players in freedom to transfer, the need to introduce bosman ruling into indonesian sports law, study case of damian linzio and bring the case to the court of arbitration for sport. This research found that Indonesia needs to apply Bosman Ruling as the pioneer of freedom of contract to Indonesian Sports Law. Bosman Ruling can be adapted in Law Number 3 of 2005 on the National Sports System in Indonesia. For Damian Linzio, author recommend to bringing the case to Court of Arbitration for Sport because they are more competent to resolve sports cases.